CALCULATION AND OPTIMIZATION THERMOELECTRIC PARAMETERS OF COMPOUNDS IV-VI (REVIEW) - Дзумедзей, Роман Олексійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Detailed analysis of methods for calculating thermoelectric parameters. Established temperature ranges dominance of different types of scattering in pure crystals of compounds IV-VI (PbS, PbSe, PbTe). The theoretical calculation of the thermoelectric parameters: mobility μ, Seebeck coefficient α, electrical conductivity σ, thermal conductivity χ, thermoelectric power α2σ, figure of merit Z, dimensionless figure of merit ZT. Particular attention is paid to ways of optimizing the main parameters of the thermoelectric material for their projected use.